Knowledge for a Sustainable World - Halvorsen, Tor; Ibsen, Hilde; M'kumbuzi, Vyvienne RP (African Minds, 2015)
The search for answers to the issue of global sustainability has become increasingly urgent. In the context of higher education, many universities and academics are seeking new insights that can shift our dependence on ways of living that rely on the exploitation of so many and the degradation of so much of our planet. This is the vision that drives SANORD and many of the researchers and institutions within its network. Although much of the research is on a relatively small scale, the vision is steadily gaining momentum, forging dynamic collaborations and pathways to new knowledge. The contributors to this book cover a variety of subject areas and offer fresh insights about chronically under-researched parts of the world. Others document and critically reflect on innovative approaches to cross-continental teaching and research collaborations. This book will be of interest to anyone involved in the transformation of higher education or the practicalities of cross-continental and cross-disciplinary academic collaboration. The Southern African-Nordic Centre (SANORD) is a network of higher education institutions from Denmark, Finland, Iceland, Norway, Sweden, Botswana, Namibia, Malawi, South Africa, Zambia and Zimbabwe. Universities in the southern African and Nordic regions that are not yet members are encouraged to join.